2016
DOI: 10.1111/1744-7917.12320
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and proteomic analyses on the supercooling ability and mining of antifreeze proteins of the Chinese white wax scale insect

Abstract: The Chinese white wax scale insect, Ericerus pela, can survive at extremely low temperatures, and some overwintering individuals exhibit supercooling at temperatures below -30°C. To investigate the deep supercooling ability of E. pela, transcriptomic and proteomic analyses were performed to delineate the major gene and protein families responsible for the deep supercooling ability of overwintering females. Gene Ontology (GO) classification and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…Elevated levels of phosphorylated‐Akt were detected in −15 °C‐exposed Ep. scudderiana larvae when compared to control larvae (Zhang & Storey, ), whereas a transcriptomics approach in overwintering Chinese white wax scale insects, Ericerus pela , detected significant changes in levels of several transcripts associated with the PI3K‐Akt signalling pathway (Yu et al ., ). Expression levels and activity assessment of key PI3K pathway effectors in cold‐exposed Colorado potato beetles would provide additional leads as to the relevance of the bantam‐3p regulated Trbl‐PI3K/Akt pathway in these insects at low temperatures.…”
Section: Discussionmentioning
confidence: 97%
“…Elevated levels of phosphorylated‐Akt were detected in −15 °C‐exposed Ep. scudderiana larvae when compared to control larvae (Zhang & Storey, ), whereas a transcriptomics approach in overwintering Chinese white wax scale insects, Ericerus pela , detected significant changes in levels of several transcripts associated with the PI3K‐Akt signalling pathway (Yu et al ., ). Expression levels and activity assessment of key PI3K pathway effectors in cold‐exposed Colorado potato beetles would provide additional leads as to the relevance of the bantam‐3p regulated Trbl‐PI3K/Akt pathway in these insects at low temperatures.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, an RNA-seq study in New Zealand stick insects showed that genes expressed under cold exposure (-5°C for 1 h) included HSPs, cuticular genes, as well as others involved in carbohydrate metabolism and physiological variation [43]. Transcriptomic and proteomic analysis in Chinese white wax scale insects ( Ericerus pela ) from different climatic regions found 2386 DEGs, involved in energy metabolism, catalytic activity, and response to stimuli [13]. …”
Section: Discussionmentioning
confidence: 99%
“…The SCP is thus an indicator of cold resistance capacity. Insect SCP can be altered through extreme dehydration, purging the gut of ice nucleators, and producing multimolar concentrations of cryoprotectants [13, 14]. …”
Section: Introductionmentioning
confidence: 99%
“…This suggests that enhancement of the Hsp70 chaperone and its partner proteins is a conserved component of winter cold hardiness among both freeze tolerant and freeze avoiding goldenrod gall insects. Similarly, elevation of hsp gene expression or HSP protein levels have been associated with cold hardiness in several other insect species (Chen et al, 2006;Rinehart et al, 2006;Yu et al, 2016;Zhang et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Burton et al, 1988;Colinet et al, 2010;Stetina et al, 2015;Tungjitwitayakul et al, 2015). Recently, however, various authors have begun to show that chaperones contribute to the natural winter diapause and/or cold hardiness of insects (Sonoda et al, 2006;Kayukawa et al, 2005;Chen et al, 2006;Kayukawa and Ishikawa, 2009;Rinehart et al, 2006Rinehart et al, , 2007Yu et al, 2016); for review also see Storey and Storey (2011) and King and MacRae (2015). Indeed, work by our group has shown that larvae of the freeze tolerant goldenrod gall fly, Eurosta solidaginis, that are often found in the same fields (or even on the same plants) as E. scudderiana, up-regulate HSPs both during the winter season when larvae are in diapause and in response to laboratory cold-acclimation (Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%